Peranan Sirkulasi dan Konsentrasi Nutrisi pada Pertumbuhan Bayam Merah (Amaranthus tricolor L) dalam otomatisasi Hidroponik Sistem NFT (Nutrient Film Technique) - aniek iriany; Muhidin; Machmudi; Farusa Anggita Risyawal Farahdina; Muhammad Arfitroh Riyadin (Folium : Jurnal Ilmu Pertanian, 2023)
Hydroponic technology is a solution to overcome the limitations of agricultural land with high production and quality. Macro and micro nutrients are elements that are useful for plant growth and development. Over-absorption of elements that contribute little to crop productivity and quality can be avoided, and fertilizer costs can be minimized by applying elements quantitatively to the nutrient solution supplied to plants. The purpose of this study was to determine the nutritional formula with macro and micro nutrients in red spinach (Amaranthus tricolor L.) with the desired plant size, so that fertilization management can be obtained. The research used several levels of nutrient concentration and circulation of water flow. At 25 hst when red spinach was harvested the nutrient concentration formula that showed the highest yield was 311 mg/l-1 nitrogen, 76 mg/l-1 phosphorus, 349 mg/l-1 potassium, 286 mg/l-1 calcium, 157 mg /l-1 magnesium, 248 mg/l-1 sulfur, 7 mg/l-1 iron, 2.9 mg/l-1 manganese, 0.6 mg/l-1 zinc, 0.6 mg/l-1 boron, 0.1 mg/l-1 copper, 0.06 mg/l-1 molybdenum. This calculation is a proper concentration to be used as a reference for sustainable hydroponic nutrient management. Keywords: nutrient concentration, red spinach, hydroponics, NFT system